2011
DOI: 10.1007/s11440-011-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mesoscale instabilities in localized granular shear using digital image correlation

Abstract: Within shear bands in sands, deformation is largely non-affine, stemming primarily from buckling of well-known force chains and also from vortex-like structures. In the spirit of current trends toward multiscale modeling, understanding the links between these mesoscale deformational entities and corresponding macroscale response will form the basis for the next generation of sand behavioral models and may also aid in efforts to understand jamming-unjamming transitions in dense granular flows in general. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…The vortex centers correlate with the peaks in rotational strain seen previously by the authors [17,18]. At the conflux between adjacent vortices, the residual displacements are in opposition and induce local volumetric contraction [26]. Interestingly, we do not see evidence of "microbands" of slip between adjacent vortices, as were seen by Alonso-Marroquin et al [8] and Tordesillas et al [15] in simulations on circular particles.…”
Section: Residual Displacementssupporting
confidence: 87%
See 4 more Smart Citations
“…The vortex centers correlate with the peaks in rotational strain seen previously by the authors [17,18]. At the conflux between adjacent vortices, the residual displacements are in opposition and induce local volumetric contraction [26]. Interestingly, we do not see evidence of "microbands" of slip between adjacent vortices, as were seen by Alonso-Marroquin et al [8] and Tordesillas et al [15] in simulations on circular particles.…”
Section: Residual Displacementssupporting
confidence: 87%
“…To further improve mapping accuracy, subsets are allowed to deform to first order (note, the pixels themselves are not physically deforming; rather, the cubic-order continuous fit to the gray level intensities is deforming). Previous research [26] has shown that DIC analysis increments used here (0.1 % axial strain or about 3 % gross shear strain across the shear band) are sufficient to accommodate first order subset deformation. However, as will be seen below, correlated grain motion such as in vortex cells occurs over longer time/strain increments than afforded by the DIC analyses.…”
Section: Digital Image Correlation (Dic)mentioning
confidence: 95%
See 3 more Smart Citations